TBC1D25 alleviates nonalcoholic steatohepatitis by inhibiting abnormal lipid accumulation and inflammation. Issue 2 (30th January 2023) - Wu, Anding; Ye, Mao; Ma, Tengfei; She, Zhigang; Li, Ruyan; Shi, Hongjie; Yang, Ling; Yi, Maolin; Li, Huoping
Abstract: Nonalcoholic fatty liver disease (NAFLD) is a strong stimulant of cardiovascular diseases, affecting one‐quarter of the world's population. TBC1 domain family member 25 (TBC1D25) regulates the development of myocardial hypertrophy and cerebral ischemia–reperfusion injury; however, its effect on NAFLD/nonalcoholic steatohepatitis (NASH) has not been reported. In this study, we demonstrated that TBC1D25 expression is upregulated in NASH. TBC1D25 deficiency aggravated hepatic steatosis, inflammation, and fibrosis in NASH. In vitro tests revealed that TBC1D25 overexpression restrained NASH responses. Subsequent mechanistic validation experiments demonstrated that TBC1D25 interfered with NASH progression by inhibiting abnormal lipid accumulation and inflammation. TBC1D25 deficiency significantly promoted NASH occurrence and development. Therefore, TBC1D25 may potentially be used as a clinical therapeutic target for NASH treatment.